2006
DOI: 10.1002/ana.20859
|View full text |Cite|
|
Sign up to set email alerts
|

Natalizumab effects on immune cell responses in multiple sclerosis

Abstract: To our knowledge, we provide first proof of concept that natalizumab diminishes migratory capacity of immune cells. Our prospective study further shows that effects of therapy likely (1) differ for distinct immune cell subsets, (2) are not sustained over current dose interval, (3) have unique profiles in individual patients, and (4) include modulation of activation threshold of immune cells. Monitoring these parameters could be relevant to ongoing safety and efficacy considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
167
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(200 citation statements)
references
References 25 publications
(28 reference statements)
15
167
1
4
Order By: Relevance
“…Natalizumab treatment has been shown to reduce the migration of leukocytes into the CNS [1,6,11,16,17], to inhibit the retention of memory-and marginal zone-like B cells within the spleen [6] and to induce a sequestration of lymphocytes, in particular activated T cells [18], and of immature B cells [4] in the peripheral circulation of MS-treated patients. However, considering the scarcity of leukocytes in the CNS compared to the periphery and the slight contribution of memory-and marginal zone-like B cells on the composition of the lymphocyte pool, it is unlikely that the reduced migration of leukocytes into the CNS and the decreased retention of specific B-cell subsets in the spleen can quantitatively affect peripheral lymphocyte count or fully explain the increase of lymphocytes observed during natalizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natalizumab treatment has been shown to reduce the migration of leukocytes into the CNS [1,6,11,16,17], to inhibit the retention of memory-and marginal zone-like B cells within the spleen [6] and to induce a sequestration of lymphocytes, in particular activated T cells [18], and of immature B cells [4] in the peripheral circulation of MS-treated patients. However, considering the scarcity of leukocytes in the CNS compared to the periphery and the slight contribution of memory-and marginal zone-like B cells on the composition of the lymphocyte pool, it is unlikely that the reduced migration of leukocytes into the CNS and the decreased retention of specific B-cell subsets in the spleen can quantitatively affect peripheral lymphocyte count or fully explain the increase of lymphocytes observed during natalizumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely, therefore, that the drug can also affect T-and B-cell output from their production sites. Furthermore, the different expression of VLA-4 on lymphocyte subpopulations, with its basal levels higher on B than on T cells, on CD8 + than on CD4 + T cells, and on memory than on naïve cells [10,11] could also imply that natalizumab treatment can differentially influence the homeostasis of lymphocyte subsets. To verify these possibilities, we monitored the changes in the number of T and B lymphocytes recently released from thymus and BM in patients treated with natalizumab by quantifying the number of T-cell receptor (TCR) excision circles (TRECs) and kappa-deleting recombination excision circles (KRECs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In interpreting our findings, several factors, particularly epidemiology of melanoma, natalizumab‐associated progressive multifocal leukoencephalopathy (PML), various aspects of the TOUCH Risk Management (RiskMAP) Action Plan, and the Safety Surveillance Program in this RiskMAP (Table 3), potential pathophysiology, and an overview of pharmacovigilance efforts for opportunistic complications of medications, should be considered 6, 7, 8, 9, 10, 11, 13, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47.…”
Section: Discussionmentioning
confidence: 99%
“…79,80,82,83 In vitro immunological studies demonstrated that natalizumab treatment resulted in approximately 40% inhibition of migration of peripheral blood mononuclear cells across fibronectin-coated Boyden chambers. 86 Stuve et al 87 quantified CSF pleocytosis in natalizumab-treated MS patients (after a median of 30 doses) and in controls, which included both untreated MS patients and other noninflammatory neurological disease controls. The numbers of white blood cells, CD4ϩ and CD8ϩ T cells, B cells and plasma cells in CSF were significantly lower in natalizumab-treated MS patients as compared with other noninflammatory neurological disease controls, whereas untreated MS patients had significantly higher frequency of all these immune cell subtypes.…”
Section: Natalizumab (Tysabri; Anti-vla-4 Ab)mentioning
confidence: 99%
“…88,89 This is a very important issue, because if the in vivo effect of natalizumab on leukocyte transmigration across the BBB is as profound, as suggested by Stuve et al, 87 and lasts more than 6 months, then one could postulate that less frequent dosing of natalizumab may be sufficient for its therapeutic efficacy and that a simple cessation of natalizumab therapy in the case of the development of PML would be unlikely to restore immune surveillance of the brain for the following 6 months. Because the immunological study by Niino et al 86 implies a much less profound effect of natalizumab on the inhibition of leukocyte trafficking, and this observation is supported by the MRI study evaluating the effect of natalizumab therapy on subtle BBB leakage within visibly nonenhancing MS lesions, 90 a longitudinal study evaluating leukocyte subtypes in the CSF of MS patients before and after natalizumab therapy is needed to provide definitive answers on the magnitude and duration of the inhibitory effect of natalizumab on CNS immuno-surveillance. Interestingly, a follow-up study by Stuve et al 91 demonstrated that natalizumab therapy leads to a decrease in CSF CD4ϩ/CD8ϩ Tcell ratio to the levels that are comparable with those observed in the CSF of patients with AIDS.…”
Section: Natalizumab (Tysabri; Anti-vla-4 Ab)mentioning
confidence: 99%